Implementation of Public Relations Management in Improving Madrasah Quality - Aisyah, Siti; Fajri, Muhammad Rizkal (Development: Studies in Educational Management and Leadership, 2023)
This study aims to find out how to improve the quality of quality in madrasah through public relations. In achieving this goal, researchers use a qualitative research approach with a descriptive method. Data collection techniques are carried out through interviews with madrasah heads, teachers, especially those who play an important role in the public relations department (WKM Humas) in schools and students. This research was conducted at MAN 2 Deli Serdang Kec. Lubuk Pakam, Deli Serdang District, North Sumatra. The results of this study are about 1). Basic Concepts of Madrasah Public Relations Management, 2). Study of Madrasah Quality Problems, 3). Implementation of Effective Public Relations Management, 4). Public Relations Management Model in Improving Quality. The stages in improving quality have a major impact on the role of public relations. The good and bad of madrasah can also be determined from good public relations as well, such as socialization of madrasah with the surrounding community (participating in community activities, opening ramadhan safari events, etc.).